A new method for analysis of the modal characteristics of small rectangular rooms - Błaszak, M. A. (Archives of Acoustics, 2006)
The main aim of the study was to compare acoustic comfort in eighteen rectangular classrooms, using a new method for modal analysis. Taking into regard the Schroeder frequency as the upper frequency limit, a statistical fluctuation in frequency spacing was calculated for all modes (parameters A and B) and axial modes separately (parameters C and D). Considering the range extended by about 30% towards higher frequencies, when compared to Bolt assumptions, it appeared that the rooms did not satisfy the Bolt criterion changed significantly their modal regularity. The enclosure with the ideal proportions, according to R.H. Bolt (1 : 1.5 : 2.5) had the A value higher than a few rooms of other proportions and hence, was characterized by greater statistical fluctuation in frequency spacing.